Suppression of thymosin β10 increases cell migration and metastasis of cholangiocarcinoma - Sribenja, Sirinapa (BioMed Central, 2013)
BACKGROUND: Thymosin β10 (Tβ10) expression is associated with malignant phenotypes in many cancers. However, the role and mechanisms of Tβ10 in liver fluke-associated cholangiocarcinoma (CCA) are not fully understood. In this study, we investigated the expression of Tβ10 in CCA tumor tissues and cell lines as well as molecular mechanisms of Tβ10 in tumor metastasis of CCA cell lines. METHODS: Tβ10 expression was determined by real time RT-PCR or immunocytochemistry. Tβ10 silence or overexpression in CCA cells was achieved using gene delivery techniques. Cell migration was assessed using modified Boyden chamber and wound healing assay. The effect of silencing Tβ10 on CCA tumor metastasis was determined in nude mice. Phosphorylation of ERK1/2 and the expression of EGR1, Snail and matrix metalloproteinases (MMPs) were studied. RESULTS: Ten pairs of CCA tissues (primary and metastatic tumors) and 5 CCA cell lines were studied. With real time RT-PCR and immunostaining analysis, Tβ10 was highly expressed in primary tumors of CCA; while it was relatively low in the metastatic tumors. Five CCA cell lines showed differential expression levels of Tβ10. Silence of Tβ10 significantly increased cell migration, invasion and wound healing of CCA cells in vitro; reversely, overexpression of Tβ10 reduced cell migration compared with control cells (P<0.05). In addition, silence of Tβ10 in CCA cells increased liver metastasis in a nude mouse model of CCA implantation into the spleen. Furthermore, silence of Tβ10 activated ERK1/2 and increased the expression of Snail and MMPs in CCA cell lines. Ras-GTPase inhibitor, FPT inhibitor III, effectively blocked Tβ10 silence-associated ERK1/2 activation, Snail expression and cell migration. CONCLUSIONS: Low expression of Tβ10 is associated with metastatic phenotype of CCA in vitro and in vivo, which may be mediated by the activation of Ras, ERK1/2 and upregulation of Snail and MMPs. This study suggests a new molecular pathway of CCA pathogenesis and a novel strategy to treat or prevent CCA metastasis.